Βιβλιογραφικό σημείωμα: The Reception of Byzantium in European culture since 1500, edited by P. MARCINIAK and D. C. SMYTHE, London and New York 2016 (first issued in paperback 2019) - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2021)
Βιβλιογραφικό σημείωμα: The Reception of Byzantium in European culture since 1500, edited by P. MARCINIAK and D. C. SMYTHE, London and New York 2016 (first issued in paperback 2019)